Barriers and Supports to Parent Involvement and Collaboration During Transition to Adulthood. (November 2019) - Francis, Grace L.; Regester, April; Reed, Alexandra S.
Parent involvement and parent–professional collaboration influence positive transitions from school into adult life among young adults with disabilities. However, parents frequently report being uninformed and uninvolved in transition planning and there is a paucity of information on how to develop these relationships in high school and postsecondary settings. The purpose of this study was to investigate the perspectives of parents of young adults who graduated from a postsecondary education program. We conducted semistructured interviews with 26 parents of young adults with intellectual and developmental disabilities who graduated from a postsecondary education program in the United States. Participants identified five primary barriers to parent–professional collaboration and six strategies to support parent involvement and collaboration. Implications for practice and research are discussed.